Paradoxical Role of Glypican-1 in Prostate Cancer Cell and Tumor Growth - Quach, Nhat D. (Sci Rep, 2019)
Recent studies suggest that glypican-1 (GPC-1) is a biomarker for prostate cancer, but there are few studies elucidating the role of GPC-1 in prostate cancer progression. We observed high expression of GPC-1 in more aggressive prostate cancer cell lines such as PC-3 and DU-145. While inhibition of GPC-1 expression in PC-3 cells decreased cell growth and migration in vitro, it surprisingly increased cell proliferation and migration in DU-145 cells, suggesting that the role of GPC-1 is cell type-dependent. Further, GPC-1 inhibition increased PC-3 tumor size in NCr nude mice xenografts. We hypothesized that the discrepancy between the in vitro and in vivo data is mediated by stromal cells in the tumor microenvironment. Thus, we tested the effect of tumor conditioned media (TCM) on gene expression in human mesenchymal stem cells and fibroblasts. Treatment of stromal cells with TCM from PC-3 cells transfected with GPC-1 shRNA increased the expression of migration markers, endocrine/paracrine biomolecules, and extracellular matrix components. Additionally, the decreased cell growth in GPC-1 knockdown PC-3 cells was rescued by coculturing with stromal cells. These data demonstrate the paradoxical role that GPC-1 plays in prostate cancer cell growth by interacting with stromal cells and through ECM remodeling and endocrine/paracrine signaling.